2018
DOI: 10.1111/wvn.12326
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Childbirth, Postpartum Depression, and Birth‐Related Variables as Predictors of Posttraumatic Stress Disorder After Childbirth

Abstract: Background: Childbirth may be a significant cause of postpartum posttraumatic stress disorder (PTSD) in women.Aims: The objective of this study is to examine the effect of fear of childbirth, postpartum depression, and certain birth-related variables on postpartum PTSD. Methods:This study is a cross-sectional study. The study was carried out in a maternity hospital nonstress unit between December 1, 2015, and February 29, 2016. Three hundred and one pregnant women who met the criteria for inclusion in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
4
30
0
2
Order By: Relevance
“…In this study, women who had developed complications during or immediately after birth obtained higher PP-PTSD scores, and this finding is consistent with the literature 14,17,19,28,29 ; indeed, some complications and interventions are inevitable during childbirth.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, women who had developed complications during or immediately after birth obtained higher PP-PTSD scores, and this finding is consistent with the literature 14,17,19,28,29 ; indeed, some complications and interventions are inevitable during childbirth.…”
Section: Discussionsupporting
confidence: 92%
“…11 Other studies that have assessed PP-PTSD symptoms have reported figures that range from 3% to 39%. 7,13,14 These rates may have varied widely because the studies used different samples and examined different phases of the postpartum period. There was a strong correlation between the CityBiTS and EPDS scores, and this finding is similar to those that have previously been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations